Reporting Australia's forest biodiversity I: forest-dwelling and forest-dependent native species. Issue 3 (3rd July 2018) - Davey, S. M.
ABSTRACT: Species-level indicators based on the Montreal Process criteria and indicators framework are used to report Australia's progress towards sustainable forest management, in national and international reporting of Australia's forest biodiversity status and trends. This paper reviews the historical development of these indicators and related databases. A recent major development has been the establishment of a comprehensive suite of national inventory databases on Australia's native forest-dwelling vertebrate fauna and vascular flora for reporting in the Australia's State of the Forests Report series. Although these databases are incomplete, nearly 17 000 species records of vascular plants and over 2000 vertebrate species records have been assembled. Of the 2212 records of forest-dwelling vertebrate species, half (1101 species) are forest-dependent species that require a forest habitat for at least part of their lifecycle. Based on the frequency of habitat-use records, eucalypt open forest and eucalypt woodland forest are the most important habitat types for both forest-dwelling and forest-dependent vertebrate species. Monitoring of species varies nationally and across states and territories, with the most comprehensive approach undertaken in south-west Western Australia. Improved application of these databases to the reporting of species indicators will require improved collection of species records, inclusion of habitat data in records, and analysis of these records as time series with changing forest cover and condition. These databases also have application for informing forest-related indicators for the 2020 Aichi Biodiversity Targets of the Convention on Biological Diversity.